Polityczna funkcja muzyki. Antyteza estetyki autonomii dzieła muzycznego - Massaka, Iwona (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
This paper contains – in the historical context – the analysis of musical forms as an efficacious and sufficiently universal means of acting, governing, assembling and putting under discipline different societies (including nations) that are considered as a unity, as well as respective society groups. Here, music is considered both as a domain accompanying political phenomena as well as phenomena that are par excellence political. It is treated as an ideological instrument used by exponents of any ideology, who apply it not only for decorative purposes but first of all for the purpose of inciting the instinct of massive solidarity, enthusiasm, unanimous will and belief. The presentation is a polemic on the belief that prevails in the research on musicology that musical production is autonomous and it is considered exclusively as an act of free expression.